EFEKTIFITAS KOLEKTOR ENERGI SURYA PADA KONFIGURASI PARALEL SERPENTINE - W, Danny Syamsu; Selleng, Kristian; Mustofa, Mustofa (MEKTEK, 2012)
This study aims to demonstrate the effectiveness of the collector on the fluid mass flow rate variations in sunlight collectors on the configuration of the combined 'parallel-serpentine'. Value of the mass flow rate is 0.09, 0.18 and 0.36 ltr/min. Fluid drained from the reservoir of cold water through the collector pipe and into the parallel configuration serpentine configuration and then stored in the hot water tank. The test results showed that the efficiency of a mass flow rate achieved at the optimum 0.36 liter / min. This result is probably leading to suitable for domestic purposes.